The Covid-19, Policy And Capital Market: Empirical Evidence From Indonesia - Sri Retnoningsih; Ahmad Maulin Naufa (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This paper aims to examine the impact of Covid-19 on the Indonesian capital market. Second, we test whether any policy from regulators could mitigate its effects. By using daily time-series data from January to July, we propose the simplest regression model (ordinary least squares) to test its effect. We also conducted some robustness with various sectors and splitting samples to make sure that our findings are robust and consistent. We find that Covid-19 (proxied by new cases, cumulative cases, new deaths, and cumulative deaths) has a negative effect on stock price in all indexes, i.e., composite, Islamic, and all sectors (the worst in the financial sector). In other words, a higher number of Covid-19 leads to a lower stock price in Indonesia. Second, the regulations from the government (the President, Financial Service Authority, Central Bank of Indonesia, and Indonesian Stock Exchange) could reduce its negative impact. It means that the negative effect of Covid-10 on the Indonesian stock market is becoming lower after including policies from all regulators. Hence, measuring Covid-19’s drawbacks on the capital market by relevant policies in Indonesia. It is also quite pivotal to explore which one policy either effective or ineffective to mitigate Covid-19.